Postoperative atrial fibrillation after mitral valve replacement using left atrial versus trans-septal approach in rheumatic mitral lesion - Morsy, Ahmed Adel; Torky, Mohammad Abdelmoneim (International journal of health sciences, 2021)
Background: Mitral valve replacement (MVR) is a common surgical intervention for rheumatic mitral valve disease, with two widely used surgical approaches: left atrial (LA) and trans-septal (TS) approaches. Despite improved exposure of mitral valve in TS approach, it has been associated with an increased risk of postoperative atrial fibrillation (AF) and other complications. This study aims to compare postoperative outcomes, including AF, between LA and TS approaches in patients undergoing MVR for rheumatic mitral lesions. Methods: A retrospective study was conducted on 180 patients who underwent MVR for rheumatic mitral lesions at Tanta University Hospitals between 2017 and 2021. patients were grouped into two matched cohorts (n=75 each) based on propensity score: Group A (TS approach) and Group B (LA approach). Data on demographic characteristics, intraoperative details, and postoperative outcomes, including incidence of AF, were collected. Results: Patients in TS group had significantly longer intubation durations (20.4 ± 2 vs. 13.1 ± 1.46 hours, p < 0.001), ICU stays (4 ± 0.83 vs. 1.9 ± 0.81 days, p < 0.001), and hospital stays (12.1 ± 2.07 vs. 9.3 ± 1.78 days, p < 0.001). Postoperative AF occurred more frequently in TS group (42.67% vs. 13.33%, p < 0.001).